Comparison of gadofosveset (Vasovist®) with gadobenate dimeglumine (Multihance®)-enhanced MR angiography for high-grade carotid artery stenosis - Amarteifio, Erick; Böckler, Dittmar; Attigah, Nicolas; Demirel, Serdar (Journal of neuroradiology, 2015)
Summary: Objective To prove superiority of blood pool contrast agent gadofosveset over conventional contrast agent gadobenate dimeglumine for assessment of stenotic internal carotid artery (ICA). Methods: Eleven patients with high-grade ICA stenosis (≥ 75%), confirmed by duplex sonography, underwent MR angiography (MRA) with gadofosveset and gadobenate dimeglumine. Results: Agreement in stenosis grade was reached in 7 of 10 stenotic ICAs. In two ICAs, gadobenate dimeglumine led to underestimation of stenosis grade. There was a significant difference in signal intensity (pre-/post-stenotic segments), showing higher values for gadofosveset (P < 0.01; P < 0.05). Impression of contrast intensity with gadofosveset was better in 8 ICAs and only in 1 ICA with gadobenate dimeglumine (P < 0.05). Conclusion: Gadofosveset-enhanced MR angiography may be superior for assessment of high-grade ICA stenosis compared with gadobenate dimeglumine MR angiography.